Combination of research questions and methods: A new measurement of scientific novelty. Issue 2 (May 2022) - Luo, Zhuoran; Lu, Wei; He, Jiangen; Wang, Yuqi
Highlights: Introduce a new approach to measuring paper's novelty from the viewpoint of question-method combination. A life-index novelty measurement based on the frequency and age of terms is demonstrated. A novelty measurement algorithm based on the semantic similarity of terms is proposed. The effectiveness of the two proposed methods is demonstrated by case studies and statistical analysis. Abstract: As critical building blocks of scientific research, research questions and research methods are put forward to reveal the nature of a publication's scientific novelty. Although existing studies have examined scientific novelty from multiple combination-based views, the temporal and semantic complexity of research questions and methods remains to be fully addressed. To remedy this, we introduce a new approach to measuring the novelty of papers from the perspective of question-method combination. Specifically, we demonstrated a life-index novelty measurement based on the frequency and age of question terms and method terms. Furthermore, by using deep learning and representation learning techniques, we proposed a semantic novelty measurement algorithm based on the semantic similarity of terms. By using the dataset of papers collected from ACM Digital Library for evaluation, the effectiveness of our methods was evaluated by case studies and statistical analysis. Our work innovatively integrates the age, frequency, and semantics of research methods and research questions that characterizes novelty in scientific publications.